Penggunaan Podcasts untuk Meningkatkan Kemampuan Mendengarkan Peserta Didik - Nurwahdaniah; Ari Prasetyaningrum; Fathurrohman (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This study is aimed to investigate the use of podcasts to enhance the listening ability of seventh-grade students of SMPN 5 Selong. The research design used in this study is Classroom Action Research (CAR). The CAR phases adopted from Kemmis and McTaggart (1988) consisted of planning, implementing, observing, and reflecting. The participants of this study were 20 seventh graders of the 2022/2023 academic year. This study was held directly in SMPN 5 Selong in four meetings. The researcher collected the data from listening tests, observation sheets, and interview guides. Listening tests were held in the preliminary test and the final meeting. The finding showed that there was an improvement in students’ scores. The criterion of success was based on the school's minimum score. The score average in the final test was 85.3 and it achieved the criteria of success. Using podcasts helped students to enhance their listening ability since it was accessible and applicable to be used inside and outside the classroom